Komunitas yang Mengampuni: Menafsirkan Pengampunan Publik dalam 2 Korintus 2:5-11 dengan Metode Interkontekstual - Yudit Tiwery Weldemina; Vincent Kalvin Wenno (Indonesian Journal of Theology, 2023)
Public forgiveness plays a crucial role in efforts to reduce conflicts. In practice, forgiveness performed by a group or community often becomes the subject of diverse discourses. The text of 2 Corinthians 2:5-11 conveys a message about the necessity of forgiveness in a public context. The text is closely associated with the dynamic relationship between Paul, the community, and the individuals considered guilty. Paul makes a demand for the community to forgive those who have committed wrongdoings, following the example of forgiveness that he has demonstrated towards the offenders. Employing an intercontextual method, this study examines the context of public forgiveness in 2 Corinthians 2:5-11 and the forgiveness process that occurs in the post-conflict situation in Maluku. Both contexts are treated as subjects that collectively contribute creatively to determining meaning within this research. Considering both contexts, this study elaborates on the experiences of forgiveness in these two contexts simultaneously. Ultimately, the study deduces that public forgiveness is also important to be considered in reconciliation efforts. Forgiveness is not solely confined to the dimensions of personal piety or personal morality, but it also serves as a moral value that must be implemented by the entire community.